2019
DOI: 10.2134/agronj2019.08.0600
|View full text |Cite
|
Sign up to set email alerts
|

On‐farm Performance and Farmers’ Perceptions of DroughtTEGO‐Climate‐Smart Maize Hybrids in Kenya

Abstract: Maize (Zea mays L.) productivity in the sub‐Saharan Africa is constrained by biotic and abiotic stresses that reduce yield. In the region, one of the most serious abiotic factor is frequent intermittent droughts, which has been attributed to climate change. The purpose of this paper was to use on‐farm demonstration studies and farmer field days to demonstrate new drought mitigation technology and provide information on how small farmers can reduce yield losses. A total of 4814 demonstration plots of 39 Drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Demonstration on‐farm trials on farmer fields can be effective in adoption of drought tolerant maize hybrids in Sub‐Saharan Africa. Approximately 5000 demonstration plots of 39 drought tolerant hybrids were tested on farmers’ fields in Kenya (Obunyali et al, 2019). Drought impact on maize yield could be reduced by planting drought tolerant hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Demonstration on‐farm trials on farmer fields can be effective in adoption of drought tolerant maize hybrids in Sub‐Saharan Africa. Approximately 5000 demonstration plots of 39 drought tolerant hybrids were tested on farmers’ fields in Kenya (Obunyali et al, 2019). Drought impact on maize yield could be reduced by planting drought tolerant hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…This came as a unique observation. In Zimbabwe, Mukanga et al (2011) reported that farmers preferred local maize Although the present study depicts hybrids as 'not good' on flour properties, farmers in Kenya chose hybrid (Drought-TEGO) because of its stay-green characteristic, resistant to lodging, whiteness of flour, drought resistance and easy shelling (Obunyali et al, 2019). Other factors in favour of local maize observed outside African region include special flour flavour, sweet green maize and local prestige (Boef et al, 2013).…”
Section: Farmer's Perception Of Local Hybrid and Opv Maizementioning
confidence: 57%
“…H614 is one of the oldest cultivars and is popular among farmers, especially in high-altitude regions (Almekinders et al, 2021). According to Obunyali et al, (2019), new cultivars are slowly being adopted due to a lack of performance data under farmers' conditions. The assertion suggests that evaluating various cultivars in different production conditions is crucial for agrotechnology transfer and farmers' adoption.…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 99%